Pengembangan Aplikasi Pencarian Kontraktor Bangunan Berbasis Android - Sayyid Ali Akbar Haraki (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to create an Android operating system application that can assist the public in searching for contractors for the construction or renovation of a building. People who want to carry out development can be free to choose which contractor is suitable for service based on the experience and achievements of the contractor. In this application includes the search for contractors, adjusting funds directly with the contractor, planning work schedules directly with the contractor. The method used is the Rational Unified Process (RUP) with UML modeling and using flutter and laravel in making applications. The RUP stages carried out in int research are business modeling, system requirements analysis, design, implementation, system testing, and deployment. System testing is done by black box testing and user acceptance test (UAT). The results of the study are Android-based building contractor search applications.